Effect of sodium bicarbonate and beta-alanine supplementation on maximal sprint swimming - Mero, A. A.; Hirvonen, P.; Saarela, J.; Hulmi, J. J.; Hoffman, J. R.; Stout, J. R. (Journal of the International Society of Sports Nutrition, 2013)
This study examined the effect of simultaneous supplementation of extracellular buffer sodium bicarbonate (SB) and intracellular buffer beta-alanine (BA) on maximal sprint swimming. Methods: Thirteen competitive male swimmers completed 4 different treatments (placebo [PL], SB, BA?+?PL, and BA + SB) in a crossover procedure. PL or SB supplementation (0.3 g/kg body weight) was ingested 60 min before two maximal 100-m freestyle swims that were performed with a passive recovery of 12-min between each swim. Because of the known long washout period for carnosine, four weeks of BA supplementation (4.8 g per day) was started after the first week of PL or SB supplementation and performance testing. Results: The first maximal swims were similar, but the increase in time of the second versus the first 100-m swimming time was 1.5 s more (p < 0.05) in PL than in SB. Blood pH values were significantly (p < 0.05) greater in the SB and in the BA + SB groups compared to the PL and BA + PL values. There were no differences in peak blood lactate between the treatments. Conclusion: Supplementing with SB prior to performing maximal sprint swimming with repetitions under 60 s improves performance. However, co-supplementation with SB and BA did not confer any added benefit on maximal swim performance.